PERSEPSI GURU TENTANG KEPEMIMPINAN KEPALA MADRASAH TERHADAP DISIPLIN TERHADAP KINERJA GURU - Aminah, Siti (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
This study explores the influence of teachers' perceptions of school leadership and discipline on their performance at MTs Nurul Falah Batang Asai. The research employed a descriptive quantitative approach, using questionnaires to gather data from 34 teachers. These questionnaires were designed to assess teachers' perceptions of school leadership and their level of discipline. The results reveal a significant positive relationship between teachers' perceptions of school leadership and their performance (rx1y = 0.335, t = 2.012, β = 0.164), indicating that a positive view of school leadership can lead to improved teacher performance. Similarly, there was a significant correlation between discipline and teacher performance (rx2y = 0.629, t = 0.164, β = 0.036), suggesting that teachers who maintain higher levels of discipline tend to perform better in their teaching roles. Additionally, the study found that the combined effect of leadership and discipline accounted for 18.8% of the variation in teacher performance. This significant contribution highlights the importance of addressing both leadership perceptions and discipline as key strategies for enhancing teacher effectiveness. The findings underscore that improving teachers’ perceptions of school leadership, alongside fostering a disciplined teaching environment, are crucial for the development of teacher performance. These results are in line with previous research, which emphasizes the role of effective leadership and disciplined work environments in optimizing teacher output. This research provides valuable insights for school administrators and policymakers in formulating strategies to enhance teaching effectiveness.